THE RELATIONSHIP BETWEEN SLEEP QUALITY AND QUALITY OF LIFE IN HEMODIALYSIS PATIENTS - Helza Risdianti; Aurelia Firstania; Tsania Ayu Zaharany; Sartika Rajagukguk; Annisa Pratiwi Gunawan; Rahmawati Dian Nurani; Dinda Nur Fajri Hidayati Bunga; Risyda Marifatul Khoirot; Tobi Pitora (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Hemodialysis therapy has physical and psychological effects that can affect patients' sleep quality and quality of life and exacerbate their condition. Poor quality of life affects patients' sleep quality, partly due to anxiety or stress. If hemodialysis patients experience many problems, it will affect their quality of life, including disruption to their daily activities. The purpose of this study is to determine the relationship between sleep quality and quality of life in hemodialysis patients. Methods: This study uses correlation and a cross-section. It uses PSQI and the European Quality of Life 5 Dimensions. We used purposive sampling. There were 42 hemodialysis patients. Data collection was conducted in October 2024 at the PMI Hospital in Bogor City.Results: A total of 34 (81%) hemodialysis patients experienced poor sleep quality, while 16 (38.1%) experienced a moderate quality of life, and 9 (21.4%) experienced a low quality of life. There was a relationship between sleep quality and quality of life in hemodialysis patients, with a p-value < 0.004 and a correlation of -.435**.Conclusion: This means that poor sleep quality in hemodialysis patients will have an impact on their moderate to low quality of life. Sleep quality plays an important role in improving the quality of life of hemodialysis patients. Hemodialysis patients can improve their sleep quality by creating a sleep schedule, exercising regularly, getting exposure to sunlight, and sleeping when they feel sleepy so that they do not feel tired.